Pengaruh nilai ujian nasional, kedisiplinan, dan motivasi belajar terhadap hasil belajar bahasa Indonesia siswa SMP di Kecamatan Pandak - Purwanti, Sri; Pardimin, Pardimin (Rafandha Press, 2024)
Background: Indonesian as a subject is not only important in academic aspects, but also plays a role that is influenced by external and internal factors, external factors such as National Examination scores, internal factors such as discipline and motivation to learn. Purpose: This study was conducted to determine the influence of the Indonesian Language National Examination Score, discipline, and learning motivation on the learning outcomes of Indonesian Language students in junior high schools throughout Pandak District. Method: The research is survey research with cross-sectional method. The population in this study were 658 grade VIII junior high school students in Pandak District, including SMP Negeri 1 Pandak, SMP Negeri 2 Pandak, SMP Negeri 3 Pandak, SMP Negeri 4 Pandak, and SMP